STRATEGIC DEVELOPMENT OF COMMUNITY-BASED AGROTOURISM IN SUBAK LEPUD - I Dewa Ayu Tita Permata Tabita; I Gusti Agung Sasih Gayatri (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Mass tourism development tends to prioritize economic growth while neglecting environmental sustainability. At the same time, the potential use of agricultural products for the tourism sector has not yet been fully developed. Developing alternative tourism by integrating agriculture into tourism activities as an agrotourism a viable option for achieving sustainable development. This study aims to identify the agricultural potential of Subak Lepud in Baha Village and to formulate strategies for developing as agrotourim. Research data were collected through observation and interviews and analyzed using SWOT analysis. Based on the SWOT analysis, strategies to build synergy between agriculture and tourism in Subak Lepud include: a) developing tourism attractions based on agricultural activities and rituals within the subak system; b) expanding market opportunities by leveraging the strengths of local wisdom embedded in the subak system and utilizing agricultural products and unique tourism attractions through the establishment of subak-based economic institutions; c) accelerating the empowerment of subak members by providing additional sources of income from tourism activities alongside their farming income; d) implementing incentives and disincentives regulated in awig-awig and perarem (customary rules) to control land-use conversion, optimize labor participation among subak members, and ensure the sustainability of agricultural land and the continued existence of the subak system.